Online war in Syria : fighters take to twitter and facebook - Nur Azlin Mohamed Yasin (2014)
Fighters in Syria have Twitter and Facebook accounts where they post journal-like entries updating friends and followers of their daily lives. These accounts are open to the public without any privacy settings. Why are they exposing their covers and what are the implications?